Strategi Mitigasi Perundungan di Institusi Pendidikan Islam: Studi Kasus di Pondok Pesantren - Agung Bintoro; Rina Mida Hayati; Muhammad Irsad (Bustanul Ulum Journal of Islamic Education, 2026)
This study aims to analyze the implementation of conflict management in addressing bullying among students at Darul Ishlah Islamic Boarding School Simpang V using the Thomas-Kilmann Conflict Mode Instrument (TKI) framework, which includes five modes: Competing, collaborating, compromising, avoiding, and accommodating. This research employs a qualitative approach with a descriptive method. Data collection was conducted through participatory observation, in-depth interviews, and documentation. Research informants consisted of the pesantren leader, administrators, senior students, and junior students. Data were analyzed through data reduction, data display, and conclusion drawing with source, technique, and time triangulation. The results show that the Competing mode is implemented through strict rule enforcement and educational sanctions. The collaborating mode is applied through mediation and open dialogue that builds mutual awareness. The compromising mode is used to find middle-ground solutions, avoiding for minor conflicts to prevent escalation, and accommodating to maintain harmonious relationships. The flexible combination of all five modes proves effective in creating a safe and conducive pesantren environment. This study integrates modern conflict management theory (TKI) with Islamic values (islah, ukhuwah, musyawarah) in the pesantren context, and specifically examines the handling of bullying among students, which is still rarely discussed